Elastocaloric cooling capacity of shape memory alloys – Role of deformation temperatures, mechanical cycling, stress hysteresis and inhomogeneity of transformation. (15th August 2017) - Wu, Y.; Ertekin, E.; Sehitoglu, H.
Abstract: Elastocaloric (EC) effect refers to the rapid cooling in shape memory alloys (SMAs) during reverse transformation from martensite to austenite under adiabatic conditions. We present a very comprehensive study of the EC response far extending the existing literature by studying the effect of loading states (tension and compression), long-term cycling, strain localization, and deformation temperatures in several SMAs including CuZnAl, NiTi, NiTiCu, Ni2 FeGa and NiTiHf13.3 . We found a temperature change of 14.2 °C in CuZnAl, 18.2 °C in NiTi, 15.2 °C in NiTiCu, 13.5 °C in Ni2 FeGa, and 6.95 °C in NiTiHf13.3 upon reverse transformation depending on the entropy change (as high as 60 J/kg K), the stress hysteresis, the inhomogeneity of the transformation and the number of superelastic cycles. A gradual deterioration of the EC effect in tension develops, while in compression the EC effect can be sustained much longer (in excess of 10 4 cycles). The Ni2 FeGa SMAs possess an operational EC temperature window of nearly 200 °C, which is the widest among the chosen SMAs. With over one hundred experiments reported in one study, this paper represents an authoritative summary of the EC capabilities of a wide range of SMAs. Graphical abstract: Image 1